ANTI-CORRUPTION MEASURES FOR CORPORATE SECURITY - Georgieva Hadji Krsteski, Nataša (Journal of process management and new technologies, 2017)
Corporate security should commit to ethical management and raising the quality of companies and markets through improving cooperation and transparency by applying anticorruption measures such as accepting a code of ethics; respect and follow international business principles for dealing with bribery; improve their transparency - via access to information; involvement in politics to protect persons who disclose corruption cases; and improving corporate governance - through active mutual discussions on adjustment of legal regulations. Research methods used in the paper are: qualitative analysis of secondary data obtained from relevant institutions. Results obtained from the survey include fighting corruption in corporations must find a unique solution that is long-term strategy developed transparent society crucial criteria and principles to meet the political criteria by the fulfillment of anti-corruption standards; it requires continuous cooperation of public and private sector, NGOs and the general corpus of all stakeholders in the country against corruption; the lack of a legal framework or platform for establishing public and private partnerships, is an important factor for anti-corruption measures to improve corporate governance; mechanisms for cooperation does not seem sufficiently developed between the public, private, political and civil society; the most important factor to tackle corruption is to adopt a law on public prosecutors and determination of higher norms and standards. Conclusions drawn from the survey: in the area of ​​pre-trial procedure requires shifting responsibilities of Interior Ministry body training in the area of ​​the judicial system; it is necessary to change the Criminal Code and Criminal Procedure Code by changing certain legal provisions which refer to the Agency for money laundering SCCP, a financial police and overall legislation.